2010
DOI: 10.1167/iovs.09-4834
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI Signal Changes in Primary Visual Cortex Corresponding to the Central Normal Visual Field of Patients with Primary Open-Angle Glaucoma

Abstract: Glaucomatous neuropathy from POAG may lead to decreased cortical activity in the primary visual cortex, which corresponds to the central normal visual field. The resultant cortical depression is not related to interocular differences in results of polarimetry, OCT, and ophthalmoscopy, but is negatively correlated with PSD of visual field analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 57 publications
7
72
1
Order By: Relevance
“…The differences are however not significant which could probably be due to insufficient number of participants for comparisons (Qing et al 2010). In a previous study (Qing et al 2010), it has been determined that the activated voxels (2086 ± 1063) in visual cortex obtained from participants that visualized the stimuli using their glaucomatous eye did not differ (p = 0.428) from activated voxels (1813 ± 1239) obtained from participants with normal vision. Further investigation indicated that all glaucomatous participants visualizing using their glaucomatous eye evoked a smaller BOLD response as compared to visualizing through their fellow eye.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The differences are however not significant which could probably be due to insufficient number of participants for comparisons (Qing et al 2010). In a previous study (Qing et al 2010), it has been determined that the activated voxels (2086 ± 1063) in visual cortex obtained from participants that visualized the stimuli using their glaucomatous eye did not differ (p = 0.428) from activated voxels (1813 ± 1239) obtained from participants with normal vision. Further investigation indicated that all glaucomatous participants visualizing using their glaucomatous eye evoked a smaller BOLD response as compared to visualizing through their fellow eye.…”
Section: Discussionmentioning
confidence: 90%
“…The decrease of BOLD response evoked by the glaucomatous eyes may be due either to a flow-on effect of early perceptual loss or to cortical abnormalities. (Qing et al 2010). Thus, the POAG patients may face a complexity in their daily visual tasks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations